Relationship between serum response factor and androgen receptor in prostate cancer. Issue 15 (7th August 2015) - Prencipe, Maria; O'Neill, Amanda; O'Hurley, Gillian; Nguyen, Lan K.; Fabre, Aurelie; Bjartell, Anders; Gallagher, William M.; Morrissey, Colm; Kay, Elaine W.; Watson, R. William
<x xml:space="preserve">Abstract</x> BACKGROUND Serum response factor (SRF) is an important transcription factor in castrate‐resistant prostate cancer (CRPC). Since CRPC is associated with androgen receptor (AR) hypersensitivity, we investigated the relationship between SRF and AR. MATERIALS AND METHODS Transcriptional activity was assessed by luciferase assay. Cell proliferation was measured by MTT and flow cytometry. Protein expression in patients was assessed by immunohistochemistry. RESULTS To investigate AR involvement in SRF response to androgen, AR expression was down‐regulated using siRNA. This resulted in the abrogation of SRF induction post‐DHT. Moreover, DHT stimulation failed to induce SRF transcriptional activity in AR‐negative PC346 DCC cells, which was only restored following AR over‐expression. Next, SRF expression was down‐regulated by siRNA, resulting in AR increased transcriptional activity in castrate‐resistant LNCaP Abl cells but not in the parental LNCaP. This negative feedback loop in the resistant cells was confirmed by immunohistochemistry which showed a negative correlation between AR and SRF expression in CRPC bone metastases and a positive correlation in androgen‐naïve prostatectomies. Cell proliferation was next assessed following SRF inhibition, demonstrating that SRF inhibition is more effective than AR inhibition in castrate‐resistant cells. CONCLUSION Our data support SRF as a promising therapeutic target in combination with current treatments. Prostate 75:1704–1717, 2015. © 2015 Wiley Periodicals, Inc.